Merah, hijau dan putih? Kesannya ke atas sikap dan gelagat kumpulan etnik :kajian kes di Pulau Pinang - Haslina, Binti Abu Bakar (Universiti Malaysia Sarawak, 2006)
The aim of this study is to determine the impact of color red, green, white toward different ethic groups' attitude behavior intention. Besides, it intends to determine the reaction of respondents in Penang toward the color that particularly and closely related to their ethic group